ANALISIS KEPUASAN KONSUMEN PADA RANTAI PASOK PANGAN PENDEK PRODUK SAYUR SEGAR DI KABUPATEN CIREBON - Himawati Azzahra, Alma; Rahmat Hidayat, Yayat; Budirokhman, Dodi Budirokhman (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2023)
The increasing demand for fresh vegetable products has changed consumer patterns to buy directly from producer farmers to get products easily but of good quality, then a short supply chain marketing appeared at the Griya Hidroponics Cirebon which could provide opportunities for creating consumer satisfaction. This study have a purpose to determine the effect off product quality, price and service simultan on customer satisfaction in the short supply chain of fresh vegetable products at Griya Hydroponics Cirebon and to determine the effect of product quality, price and service parsial on customer satisfaction in the short product supply chain fresh vegetables at Griya Hydroponics Cirebon. This research design uses quantitative survey methods. Analysis technique using multiple linear regression analysis, with a total sample of 80 respondents. The results showed that there was an effect of product quality, price and service simultan and parsial on consumer satisfaction in the short supply chain of fresh vegetable products at Griya Hidroponics Cirebon, dominated by product quality variables.